2022
DOI: 10.1186/s13034-022-00455-0
|View full text |Cite
|
Sign up to set email alerts
|

What stops Korean immigrants from accessing child and adolescent mental health services?

Abstract: Background Access to child and adolescent mental health services by ethnic minorities has been poorly studied. Despite rapid growth of the immigrant Korean population, evidence indicates that few Korean families utilise these services in New Zealand. Those that do tend to present late and with significant morbidity. We sought to understand barriers to service access from Korean parents’ perspectives. Method Seven focus groups were undertaken with 3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Most studies (n = 12) were qualitative, and one study used a mixed methodology. Although the review focused on both migrants and refugees, the majority of studies (n = 8) focused on refugee populations [ 26 , 33 39 ], one article focused on ‘refugee-like migrants’ (legal migrants with refugee-like backgrounds, e.g., migrant family members with refugee backgrounds) [ 5 ], one article was on “new settlers” [ 40 ], and three were on migrants [ 41 43 ]. All study participants came from low and middle-income or non-English speaking countries.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most studies (n = 12) were qualitative, and one study used a mixed methodology. Although the review focused on both migrants and refugees, the majority of studies (n = 8) focused on refugee populations [ 26 , 33 39 ], one article focused on ‘refugee-like migrants’ (legal migrants with refugee-like backgrounds, e.g., migrant family members with refugee backgrounds) [ 5 ], one article was on “new settlers” [ 40 ], and three were on migrants [ 41 43 ]. All study participants came from low and middle-income or non-English speaking countries.…”
Section: Resultsmentioning
confidence: 99%
“…Sample sizes of the studies ranged from nine to sixty participants. The length of stay of participants in Aotearoa prior to the studies also varied, with two studies not stating this information [ 35 , 43 ]. Three studies had an average of four and five years for women and men, respectively [ 33 , 34 , 38 ], one study was between three months to 21 years [ 40 ], one study between six months to three years [ 26 ], two studies with an average of 3.25 years [ 41 , 42 ] and another two studies between 1 and 19 years [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing research has found significant disparities in the healthcare provisions and access to health information between international migrants in developed countries and residents. Generally, international migrants experience lower levels of healthcare services and face restricted access to health information compared to residents (Walkden et al ., 2018; Bruzelius and Baum, 2019; Ryoko et al ., 2019; Ram et al ., 2020; Albright et al ., 2022; Park et al ., 2022). In developed countries, implementing similar policies toward the migrant population, such as New Zealand, Canada and Australia, migrant workers often encounter challenges in accessing healthcare services equivalent to those accessible to residents (Tosti et al ., 2020; Hamilton et al ., 2019; Istiko et al.…”
Section: Introductionmentioning
confidence: 99%